A comparative study on the removal of pentachlorophenol using copper-impregnated pumice and zeolite. Issue 2 (April 2018) - Rahmani, Ali Reza; Jorfi, Sahand; Asgari, Ghorban; Zamani, Fahime; Almasi, Halime; Masoumi, Zeinab
Abstract: Pentachlorophenol (PCP) is one of the phenolic compounds, which has been identified in the categories of EPA (Environmental Protection Agency) because of its high resistance and toxicity. This work studied pentachlorophenol removal from aqueous solutions through modificated pumice and zeolite with copper. The effect of operational parameters such as initial pH, adsorbent dosage, effect of particle size and effect of impregnation on the removal of pentachlorophenol was investigated. The results showed that the highest removal efficiency in pH = 6.0, pentachlorophenol concentration of 100 mg/L and optimum adsorbent dose of 0.4 g/L and 0.5 g/L were 92 and 96% for pumice and zeolite modified with copper respectively. Equilibrium time of 100 min in the modified pumice and zeolite and the Langmuir adsorption model can be used for sorption behavior in the both systems. The removal efficiency and absorption capacity increased with increasing the pumice and zeolite modified with copper. Compositional characteristic properties of zeolites of raw zeolites and raw pumice and modified with copper using XRF and SEM-EDX analysis determined. Due to low cost, possibility of easy to preparation materials such as zeolite and pumice stones, they can used in the catalyst stabilizes, as well as the basis for consolidation of different materials to remove contaminants from water and wastewater recommended.